If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(F)=(5F-6)/7
We move all terms to the left:
(F)-((5F-6)/7)=0
We multiply all the terms by the denominator
F*7)-((5F-6)=0
Wy multiply elements
7F^2=0
a = 7; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·7·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:$F=\frac{-b}{2a}=\frac{0}{14}=0$
| 4/5s+1/3s=2/45 | | -2.3=4.1+u/4 | | 10=y/7.68+4 | | -18n+8=-16n-16 | | 26b+14=-25 | | -8(-5-5n)+8=-38-3n | | X+x+163950=322250 | | 3b+3=2 | | 0.055x+5.811=0.04x+5.802 | | 22=-9(4z+2) | | y/4=53/4 | | 7+b/16=-1 | | 3/8(2x-8)=-3/4x | | x÷0.6=2.4 | | 7/4z-1/6=17/6+3/4 | | 3/8(2x-8)=-3/4 | | 2x+5/16=3/4-1/8•-1/2 | | 25-15x=0 | | 10(x=3)=-20 | | 4-x=1/6 | | -5(v+5)=-2v-31 | | -1+5x=6x-1 | | -5(v+5)=-2-31 | | -7u+34=3(u-2) | | 6(x+1)/5=3x-3 | | -2k-8+7=34 | | 2x+9(x+1)=12 | | 6–2x=5x-9x+8 | | -4x-3=-16=-52 | | 9(x+4)=7x+32 | | -16x^2+40x-24=0 | | -4z-3=-16=-52 |